2016
DOI: 10.3389/fpsyg.2016.01001
|View full text |Cite
|
Sign up to set email alerts
|

The More (Social Group Memberships), the Merrier: Is This the Case for Asians?

Abstract: While previous studies have consistently shown that belonging to multiple groups enhances well-being, the current research proposes that for Asians, multiple group memberships (MGM) may confer fewer well-being benefits. We suggest that this is due, in part, to Asian norms about relationships and support seeking, making Asians more reluctant to enlist social support due to concerns about burdening others. Overall, MGM was associated with enhanced well-being in Westerners (Study 2), but not Asians (Studies 1–3).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 83 publications
1
28
0
Order By: Relevance
“…This is because Asian cultural norms about relationships and support seeking (i.e. concerns about burdening others; Chang, Jetten, Cruwys, Haslam, and Praharso, ) can potentially make Asians more reluctant to enlist social support from their group memberships, which may help explain the inconsistent finding. As such, rather than simply assuming a positive relationship between social identification and well‐being, it may be important to consider the content of the identity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is because Asian cultural norms about relationships and support seeking (i.e. concerns about burdening others; Chang, Jetten, Cruwys, Haslam, and Praharso, ) can potentially make Asians more reluctant to enlist social support from their group memberships, which may help explain the inconsistent finding. As such, rather than simply assuming a positive relationship between social identification and well‐being, it may be important to consider the content of the identity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should directly investigate these novel findings among ex‐prisoners and other stigmatized populations. Future research should also examine whether our findings are generalizable to more collectivist cultures where multiple group memberships may not provide the same benefits (Chang, Jetten, Cruwys, Haslam, & Praharso, ).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few studies conducted using Asian samples, it was found that Asians derived fewer support resources and wellbeing benefits from identification with multiple groups relative to Westerners. This is because Asian cultural norms about relationships and support seeking (i.e., concerns about burdening others; Chang, Jetten, Cruwys, Haslam, & Praharso, 2016) can potentially make Asians more reluctant to enlist social support from their group memberships, which may help explain the inconsistent finding. As such, rather than simply assuming a positive relationship between social identification and wellbeing, it may be important to consider the content of the identity (i.e., normative expectations tied to the identity).…”
Section: Discussionmentioning
confidence: 88%
“…Chang, M. X. L., Jetten, J., Cruwys, T., Haslam, C., & Praharso, N. (2016). The more (social group memberships), the merrier: Is this the case for Asians?…”
Section: Discussionmentioning
confidence: 99%